BEYOND SALARY: HOW INTEGRATED COMPENSATION AND BENEFITS TRANSFORM RETAIL EMPLOYEE PERFORMANCE - Munawaroh Munawaroh; Ayat M. Ayatullah; Oktafia Azizah; Opan Baehaqi; Urfi Sholihat (International Journal of Multidisciplinary Research and Literature, 2026)
This research employs a qualitative approach using an integrative literature review as the primary methodology. Data were gathered through systematic examination of peer-reviewed journals, authoritative HRM textbooks, and empirical research (2020-2025). ATIQ HOMEKLIK serves as the contextual case to ground theoretical findings and develop actionable recommendations for Indonesian retail SMEs. This approach enables the synthesis of contemporary compensation theory with practical application in resource-constrained retail contexts. Findings reveal that compensation and benefits significantly influence employee motivation, job satisfaction, and performance. Fair financial compensation, combined with non-financial benefits such as career development, job security, and a conducive work environment, effectively increases employee engagement and productivity. The research introduces an integrated total rewards approach applicable to retail SMEs. Results indicate that the strategic integration of compensation and benefits is a key factor in improving employee performance and supporting organisational sustainability. This study contributes both theoretically, by strengthening the compensation-benefit-performance literature in retail SME contexts, and practically, by providing actionable strategies for effective human resource management.